Copper-catalyzed N-arylation of amines with aryliodonium ylides in water - Nabar, Kasturi U.; Bhanage, Bhalchandra M.; Dawande, Sudam G. (Beilstein Journal of Organic Chemistry, 2023)
Copper sulfate catalyzed an efficient, inexpensive, and environment-friendly protocol that has been developed for N-arylation of amines with 1,3-cyclohexadione-derived aryliodonium ylides in water as a green solvent. Aromatic primary amines substituted with electron-donating as well as electron-withdrawing groups on the aryl ring reacted smoothly with iodonium ylides to give the corresponding diarylamines with good to excellent yields. Also, secondary amines underwent N-arylation to deliver tertiary amines with moderate yields.
Keywords: amines; arylation; C–N bond formation; iodonium ylide; sustainable